Ethics and Liability of Business Actors in Providing Discounts in E-Commerce Transactions - Virginnia Melya Iskandar; P. Lindawaty S. Sewu; Daniel Hendrawan (Fakultas Hukum Dehasen, 2024)
This research aims to analyze the ethics and liability of business actors in providing discounts in e-commerce transactions. E-commerce involves various types of businesses, ranging from small online shops to large companies. With the sophistication of today's technology, it opens up opportunities to cheat for personal gain. Providing fake discounts is one of the concerns of E-Commerce users. The ethics and liability of business actors in providing discounts are the main points demanded by consumers. This research uses normative juridical approach through legislation and assessment of norms and rules applicable in Indonesia. The result of this research is that Government Regulation of the Republic of Indonesia Number 58 of 2001 concerning the Development and Supervision of the Implementation of Consumer Protection that the Government is responsible for fostering the implementation of consumer protection that ensures the acquisition of consumer and business rights and the implementation of consumer and business obligations. If it is found that business actors violate ethics, the sanctions received can be in the form of social sanctions such as damaging the reputation or good name of the company, reducing the trust of consumers and the public in the related company. The settlement of consumer disputes can be pursued through the court or out of court based on the voluntary choice of the parties to the dispute. Consumers can sue business actors in public courts individually or in groups (class action).